Evaluation of Mean Performance in Agronomic and Quality Traits of Bottle Gourd [Lagenaria siceraria (Molina)Standl.] Genotypes - Durani Sahar Hassan Tinkie; Ummyiah H. Masoodi; Gowhar Ali; Nageena Nazir; Rizwan Rashid; Gazala Nazir; Mehnaz Rashid; Lubna Rasool; Tasaduq Shabir (Archives of Current Research International, 2025)
An experiment was conducted at the Experimental Field of Urban Technological Park (Habbak), Srinagar, Jammu and Kashmir, during Kharif-2023 to assess forty-one phenotypically diverse bottle gourd genotypes, including two checks, Pusa Naveen and Pusa Santushti, for different agronomic and quality traits. The experiment was laid out in single-factor Randomized Complete Block Design with three replications. The analysis of variance showed significant differences among genotypes for all the traits. The highest fruit yield per hectare was found in SKUA-BG-35 (714.58 q), SKUA-BG-29 (654.36 q), and SKUA-BG-23 (621.77 q). The lowest fruit yield per hectare was obtained in Pusa Naveen (221.21 q), SKUA-BG-36 (237.20 q), and SKUA-BG-14 (316.61 q). The mean fruit yield per hectare over all genotypes was 485.74 q.